Features and practical experience in obtaining complex profile castings from aluminum alloys - M. A. Sadokha; A. V. Kryutsou (Литьë и металлургия)
Variants of preparation of production of castings from aluminum alloys in conditions of single and small‑scale production are considered. It is established that in order to reduce the time and cost of obtaining castings, it is most expedient to carry out end‑to‑end design and manufacture of technological equipment using additive technologies and casting in sand‑resin molds obtained using the “no‑bake” technology.